EXPLORING WRITING INSTRUCTION-BASED PROCESS WRITING APPROACH IN TERTIARY LEVEL OF EFL ARGUMENTATIVE WRITING CLASSROOM - Anak Agung Putri Maharani (Jurnal Santiaji Pendidikan (JSP), 2022)
Within the 21st century, students are demanded to argue reasonably over massive information that they receive. It is necessitated for the students to filter acceptable and reasonable information for their meaningful learning. Involving 28 sophomores in English Language Education Study Program, a descriptive qualitative research design was utilized, aimed at figuring out the impact of writing instruction-based process approach towards the students’ EFL argumentative writing skill and deciphering their responses toward writing instruction-based process approach. The respondents’ progress in argumentative writing and views were gauged to reach the conclusion. Threefold methods of collecting data were administered; observation, interview, as well as focus group discussion (henceforward, FGD). Afterwards, the data collected were filtered, presented and verified. After analyzing the collected data, it was found that writing instruction-based process approach had good impact on the students’ argumentative writing development. Then, the participants responded positively towards the writing instruction-based process approach.